Two‐phase colour‐aware multicore real‐time scheduler. Issue 4 (15th March 2017) - Gracioli, Giovani; Fröhlich, Antônio Augusto
Abstract : A two‐phase colour‐aware real‐time scheduler to reduce the contention caused by the cache coherence protocol due to accesses to shared cache partitions in a multicore processor is proposed. The first phase is a colour‐aware task partitioning (CAP) algorithm that assigns tasks that share colours to a common processor whenever possible. The second phase is a dynamic colour‐aware scheduler that detects cache coherence activities at run‐time, preventing the execution of tasks that interfere with each other and thus reducing the contention caused by the cache coherence protocol. The authors compare the proposed scheduler with a CAP without run‐time optimisation and with the best‐fit decreasing heuristic in terms of deadline misses and tardiness of several task sets using a real‐time operating system and a modern 8‐core processor. The results indicate that the proposed scheduler improves deadline tardiness and provides hard real‐time guarantees by combining cache and task partitioning with scheduling optimisations.